Liszt’s experiments with literature - Gamrat, Małgorzata (Interdisciplinary Studies in Musicology, 2018)
Liszt’s aspiration to create his own musical language and to find new tools of musical expression was unusually strong almost from the very beginning of his artistic career. Not only did the artist gladly spend his time among writers and read numerous texts, but he also turned to the technical and expressive means originating in literature. Among the most important attempts to work out new musical means on the basis of literary devices we may list: a strong emphasis on the sound factor, formal freedom and mixing of genres, composing a musical cycle on the basis of a poetic one (a narrative whole, leitmotifs), appealing to emotions by means of the appropriate selection of an oeuvre’s parameters, in particular articulation and dynamics, poetic quotations preceding the score, transposition of literary genres into the field of music, or synthesis of poetry and music in songs, symphony choruses, and piano transcriptions of songs. Album d’un voyageur is an excellent example of Liszt’s borrowings from literature and a very individual cycle with literary value. It is a story of a voyage across a small part of Europe in search of self-understanding; it is also a history of rebellion and the doubts which come as its consequence, as well as finding peace through contact with nature and through searching for God. Liszt created here an unusual oeuvre that combines poetic images and sounds. In 1884 Liszt declared that the most perfect form of synthesis of poetry and music is transcription of songs. It is here that music interprets poetry with its own means, which are often invented for the purposes of this synthesis. On the basis of the transcription of the song Ich liebe dich from 1860 we may observe how music becomes a language capable of imitating the intonation of the human voice, expressing emotions and, symbolically, relying on a programme, also expressing ideas.